2020
DOI: 10.1002/pbc.28280
|View full text |Cite
|
Sign up to set email alerts
|

Acute lymphoblastic leukemia clonal distribution between bone marrow and peripheral blood

Abstract: Acute lymphoblastic leukemia (ALL) is often composed of numerous subclones. Here we test whether the clonal composition of the blood is representative of the bone marrow at leukemia onset. Using ultra-deep IGH sequencing, we detected 28 clones across 16 patients; 5/28 were only in the marrow. In four patients, the most abundant clones differed between sites, including three in which the dominant medullary clones were minimally detectable in the blood. These findings demonstrate that the peripheral blood often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…These studies reported on 16–183 paired peripheral blood and bone marrow samples and detected a complete concordance of 69–97%. Four of these seven studies either included or were exclusively performed in patients with lymphoid neoplasms [ 40 , 42 , 44 , 45 ], five did not report how many days were allowed between the peripheral blood and bone marrow samples, two reported up to 334 days between the sampling, and the sensitivity of the NGS analyses and/or the mean (min–max) coverage were rarely reported. Nevertheless, these important studies underscore the relevance and the real-world clinical need to be able to diagnose and monitor treatment response without repeated bone marrow evaluations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies reported on 16–183 paired peripheral blood and bone marrow samples and detected a complete concordance of 69–97%. Four of these seven studies either included or were exclusively performed in patients with lymphoid neoplasms [ 40 , 42 , 44 , 45 ], five did not report how many days were allowed between the peripheral blood and bone marrow samples, two reported up to 334 days between the sampling, and the sensitivity of the NGS analyses and/or the mean (min–max) coverage were rarely reported. Nevertheless, these important studies underscore the relevance and the real-world clinical need to be able to diagnose and monitor treatment response without repeated bone marrow evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a real-world clinical need exists to be able to use an alternative or surrogate sample, to be able to obtain information on the mutational status of a patient’s disease. In this regard, research groups around the world have assessed whether the genetic information required for an integrated diagnosis and/or treatment monitoring may also be obtained from analysis of the peripheral blood of patients with various hematologic malignancies ( Table 1 and Table S1 ) [ 20 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is ideal for lymphocytic leukemias, as every T and B cell undergoes VDJ recombination to generate functional B and T cell receptors; the specific sequence of the rearrangement in the receptor is unique to an individual B or T cell. ALL results from the abnormal expansion of typically 1-5 B or T cell clones, each of which will have a unique VDJ sequence ( 11 , 12 ). ClonoSEQ uses NGS methods to sequence the genomic DNA of cells isolated from patient blood and bone marrow samples to identify clonally expanded VDJ sequences and detect as few as one leukemic blast per million cells.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is ideal for lymphocytic leukemias, as every T and B cell undergoes VDJ recombination to generate functional B and T cell receptors as part of the cell’s maturation, and the specific sequence of the rearrangement in the receptor is unique to an individual B or T cell. ALL results from the abnormal expansion of typically 1-5 T or B cell clones, each of which will have a unique VDJ sequence (10, 11). ClonoSEQ identifies clones based on a major expansion of that particular VDJ sequence within the patient’s blood and bone marrow samples at leukemia diagnosis.…”
Section: Introductionmentioning
confidence: 99%